Correlation between Overweight and Mental Health in Adolescents: A Meta Analysis - Riski Anisa; Yulia Lanti Retno Dewi; Hanung Prasetya (Journal of Epidemiology and Public Health, 2022)
Background: Adolescence is a critical period in human life because of the various changes that occur during this stage of life. Overweight and obesity in adolescents is a major public health problem in all developing countries, in addition to affecting physical health, can have a negative impact on mental health. This study aims to analyze the primary study of the effect of being overweight and obese on mental health in adolescents with a meta-analysis. Subjects and Method: This study is a meta-analysis with the following PICO, Population: teenagers. Intervention: overweight and obese. Comparison: normal weight. Outcome: mental health. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles [(adolescent OR teenager OR children) AND (“body mass index” OR BMI OR overweight OR obesity) AND (depression OR “depression symptom”) AND (anxiety OR “anxiety symptom”)]. The included articles are full text in English in 2010 to 2022 with cohort study design and report on aOR in multivariate analysis. The selection of articles is done by using PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application.Results: Nine studies were included in this study, six studies from the Americas, two studies from the European continent, and one study from the Australian continent. The data collected showed an increased risk for depression and anxiety in adolescents who were overweight and obese than adolescents who had normal weight. Obese adolescents had a higher risk of depression (aOR= 1.64; 95% CI= 1.42 to 1.90; p<0.001) than overweight adolescents (aOR= 1.09; 95% CI= 1.00 to 1.18; p= 0.050). Adolescents who were obese had a higher risk of anxiety (aOR= 1.27; 95% CI= 1.08 to 1.49; p= 0.003) than adolescents who were overweight (aOR= 1.10; 95% CI= 1.01 to 1.19; p= 0.020).Conclusion: Overweight and obesity can have an influence on the mental health of adolescents. Keywords: adolescent, overweight, obese, depression, anxiety, meta-analysis. Correspondence:Riski Anisa. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: riskianisa93@gmail.com. Mobile: +6285749027212.